Результаты экспериментальных исследований вибраций турбогенератора ТВВ-1000-2У3 энергоблока № 3 ЮУ АЭС - Шумилов, Юрий Андреевич; Демидюк, Борис Мартынович; Штогрин, Александр Валерьевич (НТУ "ХПИ", 2008)
С использованием техники вибродиагностики анализируются причины выхода из строя обмотки статора турбогенератора ТВВ-1000-2У3 энергоблока № 3 ЮУ АЭС. Показано, что существующие методы вибрационного контроля, ориентированные на отстройку элементов конструкции ТГ от частот 50 и 100 Гц, не отвечают реальному положению, поскольку заметную роль в повышенной выброактивности обмотки статора ТГ играют вибрации на частотах, кратных 50 и 100 Гц. Кроме гармонических составляющих (высших и субгармоник), необходимо считаться с шумовой составляющей вибрации, обусловленной недостаточной прессовкой сердечника статора.

Using a vibrodiagnostics technique, reasons for failure of turbogenerator (TG) TVV-1000-2U3 stator winding in THUkr nuclear power station power plant № 3 are analyzed. The existing vibration control techniques oriented towards offset of the TG construction elements from frequencies of 50 and 100 Hz are shown not to meet the real situation as vibrations at the frequencies multiple of 50 and 100 Hz play a noticeable role in increased vibroactivity of the TG stator winding. Along with harmonic components (higher ones and subharmonics), a significant role is played by the vibration noise component caused by the stator core insufficient pressing.
Results of experimental research on THUkr nuclear power station power plant № 3 turbogenerator TVV-1000-2U3 vibrations
Keywords: система первичной обработки; вибрация; турбогенератор; шумовая составляющая; turbogenerator failure; vibrodiagnostics technique; experimental research